Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1111/j.1559-1816.1973.tb01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Undergoing Arbitrary Discrimination Upon Subsequent Attitudes Toward a Minority Group1

Abstract: The purpose of the experiment was to test the hypothesis that having been both the object of prejudice and discrimination and the discriminator, a child will be less likely to hold prejudiced beliefs and exhibit discriminatory behavior toward a minority group. A 3rd‐grade class was randomly divided into Orange and Green people. On Day I, Orange children were “superior” and Green children were “inferior”. On Day II, statuses were rcvcrsed. On Day III and again 2 weeks later, the experimental class was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…A number of researchers investigated the effects of curriculum interventions such as teaching units and lessons, multiethnic materials, role-playing, and simulation on children's racial attitudes between 1969 and 1980. These investigators included Litcher and Johnson (1969), Weiner and Wright (1973), and Yawkey and Blackwell (1974). In general, these studies indicate that curriculum interventions can modify student racial attitudes if certain conditions exist in the experimental situations.…”
Section: Research On Children's Racial Attitudes: 1960 Through the 1980smentioning
confidence: 97%
“…A number of researchers investigated the effects of curriculum interventions such as teaching units and lessons, multiethnic materials, role-playing, and simulation on children's racial attitudes between 1969 and 1980. These investigators included Litcher and Johnson (1969), Weiner and Wright (1973), and Yawkey and Blackwell (1974). In general, these studies indicate that curriculum interventions can modify student racial attitudes if certain conditions exist in the experimental situations.…”
Section: Research On Children's Racial Attitudes: 1960 Through the 1980smentioning
confidence: 97%
“…Also, it may be that students with social anxiety are victims of bullying and harassment, and consequently, feel an af®nity with other students who are also victims. Past research indicates that children who have experienced prejudice themselves hold less prejudiced attitudes toward minority groups (Weiner & Wright, 1973).…”
Section: Direct and Indirect Pathways To Positive Attitudesmentioning
confidence: 99%
“…Research on high school and college students have shown that blue-eyed/brown-eyed role playing leads to diminished prejudice (Breckheimer & Nelson, 1976;Byrnes & Kiger, 1992); we are aware of only one study that has tested this approach on younger children. Weiner and Wright (1973) used an armband version of Elliot's approach (randomly assigned to wearing green or orange armbands) and found that White third graders in the role-play group were signifi cantly more likely to attend a picnic with peers than those in a control group. Note that these effects seem to be non-specifi c; children diminished their prejudice towards African American peers after participating in the role play even though the exercise did not specifi cally address ethnic issues.…”
Section: Role Playing and Empathymentioning
confidence: 99%